ЖИСМОНИЙ ТАРБИЯ ЎҚИТУВЧИЛАРИНИ КАСБИЙ КОМПЕТЕНТЛИГИНИ ШАКЛЛАНТИРИШДА МАХСУС МОБИЛ ИЛОВАЛАРДАН ФОЙДАЛАНИШ МАСАЛАЛАРИ - Олимов, А.И. (SCIENCE and SOCIETY, 2022)
This article describes the results of the analysis of the pedagogical experience of the effectiveness of using mobile applications in teaching the subject to students studying in physical education at higher educational institutions.
Keywords: students; physical cultural; physical education; mobile applications; science; performance indicators